UPAYA MENJAGA SANITASI PERALATAN MAKAN DAN MINUM DI KAFE DAMIL DENIA UNIVERSITAS NEGERI PADANG - Romana, Nicolaus Victor; Silfeni, Silfeni; Pramudia, Heru (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
The study aims to know an effort to maintain sanitation equipment to eat and drink in the Café Damil Denia Universitas Negeri Padang of the which consist of the early stages of the laundering, laundering, flushing, eradication of germs, drying, and storage equipment to eat and drink. This type of research it’s a sort of descriptive set of qualitative. The data collection is done using the method of interviews, observations, and documentation involving informants, namely management, and employee Café Damil Denia. The analysis of data in this study include the reduction of data, and the conclusion. The result of this research is (1)The eating utensils and drinking just one container. (2) Of eating utrnsils and drinking did not immediateky be appointed to the wash. (3) A cup and plate that have not been washed in clean. (4) The drink is ready to be washed and still wet laid down in the visitors. (5) Of eating utensils and drinking will be used still a stain. (6) The cleanliness of weapon to eat and drink not awake.Keyword: Sanitation of eating utensils, Cafe